2015
DOI: 10.1080/14658011.2015.1110877
|View full text |Cite
|
Sign up to set email alerts
|

Tensile, flexural and morphological properties of electron beam-crosslinked LDPE–EPDM blends

Abstract: The effect of electron beam (EB) irradiation on the tensile, flexural and morphological properties of low-density polyethylene (LDPE)/ethylene-propylene diene elastomer (EPDM) blends had been studied in the absence and presence of crosslink promoters, such as trimethylolpropane triacrylate (TMPTA) and triallyl cyanurate (TAC). Blends were prepared by melt mixing of LDPE and EPDM followed by EB irradiation at various doses. The gel fraction (%) of irradiated blends was increased with an increase in EPDM content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Similar trends in hardness have been observed as intensile strength and modulus. The pure EPDM shows hardness of 65 . In the blend composition as the percentage of SiR increases the hardness goes down.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Similar trends in hardness have been observed as intensile strength and modulus. The pure EPDM shows hardness of 65 . In the blend composition as the percentage of SiR increases the hardness goes down.…”
Section: Resultsmentioning
confidence: 98%
“…The gel fractions of blend are observed to increase by EPDM concentrations and irradiation dose. Pure EPDM shows higher gel fractions compared to all SiR/EPDM samples because the EPDM possesses higher crosslink ability due to its higher amorphousness and molecular structure …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prepared crosslinked system can be used in o-rings and gaskets applications. They have discovered that the crosslinking increases with increasing EPDM amount and E-Beam doses, which results in the higher mechanical, thermal, and flame resistance properties of the LDPE/EPDM blends system ( Chowdhury et al, 2015 ). It can be seen form comparative study of E-Beam and gamm radiation, the processing time requiredto cure polymer system usinf E-Beam is less which enhancec its output rate and requird less energy as compared to gamma radiation.…”
Section: Electron Beam Versus Gamma Radiation Processed Polymersmentioning
confidence: 99%
“…Ray Chowdhury et al reported promoted crosslinking efficiency of TMPTA compared with TAC in EPDM and LDPE-EPDM blends. 7 For peroxide cured FKM, the coagent is indispensable and prefer to be less polar structures for better solubility, 8 such as TAC, TAIC and TMAIC. In addition, TAC was describe as less stable under thermal aging 1,6 and TMAIC did not get much attention as coagent.…”
Section: Introductionmentioning
confidence: 99%